Validation of the CORINE land cover database in a pilot zone under semi-arid conditions in La Mancha (Spain) - Martín de Santa Olalla Mañas; Cabañero Soria; Artigao Ramírez (Cybergeo, 2003)
The CORINE programme (initiated in 1985) has created an Information System referring to the European Union countries, which provides administrative, geographical, land use, vegetal cover information, along with different environmental parameters (CORINE, 1994). The CORINE land cover database offers valuable information on the different land covers of the mapped areas. At present the whole Iberian Peninsula is covered by this digitised database.CORINE is a highly valued instrument in the EU countries where it has been completed. It is therefore necessary to check the quality of the information it provides taking into account the large extension, the climate and environmental variety of the mapped surface.This paper consists of an in-depth study, based on various updated sources, of the actual state of the land cover in a specific area in the central part of Castilla-La Mancha (Spain) with a surface area of approximately 10,000 sq. km. The information obtained is then compared to the CORINE data for the same area. Our aim is therefore to verify the validity of the latter in a pilot zone by using, for this purpose, databases whose definition is higher than CORINE’s and observe both its degree of updated accuracy as also the suitability of the different categories used by CORINE with the land uses and ecosystems existing today.The paper requires the choice of an appropriate scale, which depends on the nature of the study to be carried out. CORINE forms a good database for the handling of information on land cover on large working scales. The geo-referencing errors detected in the present paper have shown the difficulty of its overlapping with other databases.After the relevant comparisons, which could not be carried out by overlapping, it is proved how CORINE land covers is becoming out of date, taking into account the transformations, changes and development of the present land cover in our area.On the other hand, we consider that the nomenclature of CORINE land cover may not be sufficiently varied in its third level, especially in woodland areas. The results  in the grouping of very different formations in the same class. This does not happen, for example, in the urban areas, when a large quantity of classes exist to define the variety of  urban land uses.This study has been carried out in the setting of the Project “Modelling the effect of land degradation on climate” (ENV4-CT98-0696) financed by the European Union.